Acoustic Stimuli Can Improve and Impair Somatosensory Perception - Nuernberger, Matthias; Schaller, Denise; Klingner, Carsten; Witte, Otto; Brodoehl, Stefan (Frontiers in Neuroscience, 2022)
The integration of stimuli from different sensory modalities forms the basis for human perception. While the relevant impact of visual stimuli on the perception of other sensory modalities is recognized, much less is known about the impact of auditory stimuli on general sensory processing. This study aims to investigate the effect of acoustic stimuli on the processing of somatosensory stimuli using real noise (i.e., unpleasant everyday noise, RN) and neutral white noise (WN). To this purpose, we studied 20 healthy human subjects between 20 and 29 years of age (mean: 24, SD: ±1.9 years sex ratio 1:1). Somatosensory perception was evaluated using mechanical detection threshold (MDT) of the skin on the back of the dominant hand. To investigate the underlying mechanisms in the brain, fMRI was performed while applying acoustic stimulation (RN and WN) and tactile stimulation of the dominant hand. Here we show that acoustic stimulation with noise alters the perception of touch on the skin. We found that the effect of RN and WN differed. RN leads to an improved tactile perception, whereas WN impaired tactile perception. These changes go along with significant differences in brain activity and connectivity. WN is associated with a significant increase in brain activity in multiple brain areas such as the auditory and somatosensory cortex, parietal association cortex, and the thalamus compared to RN. With tactile stimulation of the skin, the flow of information in these brain areas is altered. While with RN the information flow from the thalamus to the somatosensory cortex is prominent, the network activity pattern changes under WN revealing an increase in interaction between multiple networks. Unpleasant noise inhibits the multisensory integration and enables a more efficient unimodal perception in the somatosensory system, improving perception. Whether this is to be interpreted as a temporary increase in phasic alertness or by a stronger filter function of the thalamus with a preference for unimodal stimuli is still open for debate.